Naturalization By Investment: A Critical Analysis and the Issue of Stateless Refugees - Minahil Saleem; Arun Barkat; Hena Parmar (`, 2026)
Naturalization by investment (NBI) is one of the modes through which states confer nationality to individuals Jus sanguinis to the stateless individuals who cross international borders in the pursuit of protection by seeking refuge in neighboring states. This research study explores the potential of NBI in achieving international recognition due to the risk of financial crimes attached to it i.e, affluent people might exploit NBI to avoid prosecution in their state of origin. To do so, they invest their illegal money to buy a new nationality and thereafter relocate. As for the stateless refugees who are in dire need of nationality, this study highlights the obligations upon host states regarding the protection of basic human rights of the. Nationality being the universal and the basic right of all individuals (including refugees), this research offers a unique perspective for the investment-led naturalization of stateless refugees. Highlighting international criticism against Naturalization by investment (NBI) schemes due to illicit financial flows and missing genuine link, this study analyzes the status of nationality conferred through monetary investment under the international law and further argues that NBI can get international recognition, if nationality is conferred through non-monetary investment. Since, stateless refugees might not be that affluent to buy a citizenship, this research explores how non-monetary investment such as investment via Human Capital can conform to state’s aspiration for offering investment citizenship. The study proposes that the global challenge of statelessness which the UNHCR had envisioned to resolve by 2024 couldn’t be tackled properly without addressing the plight of stateless refugees. Previous jurisprudence on the protection of stateless refugees is insufficient and largely unexplored. Therefore, this research provides an equitable solution to address the protection needs of stateless refugees in conformity with international law and current state practices. Keywords: Naturalization by Investment, illegal financial flows, Nationality, Stateless Refugees, Human